Effects of Shear Rate on Morphology and Gas Separation Performance as Asymetric Polysulfone Membranes - Ismail, Ahmad Fauzi; Yean, Lai Ping (ASEAN Journal of Chemical Engineering, 2002)
Asymmetric polysulfone flat sheet membranes have been produced by a dry/wet casting technique. The membranes were produced at different shear rate. Gas permeation properties were examined using pure hydrogen and nitrogen as test gases. Infrared dichroism was detected in all samples, the extent being greater in the high shear membranes. This suggests that the polymer molecules become aligned under high shear. Gas separation tests showed that the higher shear membranes exhibited greater selectivity (H!Nz)’ Some of the membrane selectivities even surpass the intrinsic selectivity of the membrane polymer. Increasing shear rate during casting had decreased skin layer thickness and thus increased pressure-normalized flux. High-shear casting also enhances the molecular orientation in skin layer and, in turn, heighten selectivity of membrane. Therefore, correlation of rheological aspects with primary phase inversion parameters provides a potential platform to develop high performance asymmetric polysulfone membranes for gas separation.